Risk of Malignancy Index Has a Poor Sensitivity in Detecting Borderline Epithelial Tumors and Non-Epithelial Ovarian Tumors - Yasin Durmus; Mehmet Mutlu Meydanli (Medical Network, 2019)
Objectives: To evaluate diagnostic accuracy of "Risk Of Malignancy İndex-1" (RMI-1) for postmenopausal adnexal masses. Study Design: Fifty postmenopausal women who had undergone surgery because of adnexal masses were included in this prospective study. RMI-1 scores were calculated through the formula: [RMI= Ultrasound Score x Menopause Score x Serum Ca-125 Level] and noted preoperatively by the same sonographer for each case. "Final histopathological diagnosis" was accepted as gold standard for benign-malignant categorical distribution. Borderline tumors were categorized in malignant tumor group. Results: According to final histopathological results; 20 of the 50 patients had malignant adnexal masses. Twelve of them had invasive epithelial tumors. The remaining 8 patients had borderline epithelial tumors or non-epithelial ovarian cancers. When the RMI score ≥200 was accepted as a positive test result compatible with the literature; we calculated the sensitivity: 75%, specificity: 93%, positive predictive value: 88%, negative predictive value: 85% predicting malignant adnexal masses. All of the 12 patients with invasive epithelial tumors had RMI-1 scores higher than 200. Nevertheless, only 3 of the 8 patients with borderline epithelial tumors or non-epithelial ovarian cancers had RMI-1 scores higher than 200. We have found out that invasive epithelial tumors had higher USG Scores, Ca-125 Levels and RMI Scores when compared to borderline epithelial tumors and non-epithelial ovarian cancers and the difference was statistically significant. Conclusions: RMI-1 is a valuable and applicable method in the initial evaluation of postmenopausal patients with adnexal masses. İt has a high diagnostic performance in detecting invasive epithelial ovarian cancers, but it has a poor sensitivity in detecting borderline ovarian tumors and non-epithelial ovarian cancers.